2020
DOI: 10.1001/jamasurg.2019.6033
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Indocyanine Green Tracer-Guided Lymph Node Dissection During Laparoscopic Radical Gastrectomy in Patients With Gastric Cancer

Abstract: IMPORTANCEThe application of indocyanine green (ICG) imaging in laparoscopic radical gastrectomy is in the preliminary stages of clinical practice, and its safety and efficacy remain controversial.OBJECTIVE To investigate the safety and efficacy of ICG near-infrared tracer-guided imaging during laparoscopic D2 lymphadenectomy in patients with gastric cancer. DESIGN, SETTING, AND PARTICIPANTSPatients with potentially resectable gastric adenocarcinoma (clinical tumor stage cT1-cT4a, N0/+, M0) were enrolled in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
192
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 222 publications
(204 citation statements)
references
References 69 publications
10
192
2
Order By: Relevance
“…retrieve more lymph nodes compared with routine surgery 16,25 . A recent randomized study demonstrated that ICG signi cantly improved the number of lymph node retrieved in D2 lymphadenectomy without increasing the risk of complications 15 . Our study consistently found that ICG could increase the number of lymph nodes retrieved during laparoscopic gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…retrieve more lymph nodes compared with routine surgery 16,25 . A recent randomized study demonstrated that ICG signi cantly improved the number of lymph node retrieved in D2 lymphadenectomy without increasing the risk of complications 15 . Our study consistently found that ICG could increase the number of lymph nodes retrieved during laparoscopic gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, ICG administration includes subserosal and submucosal injections around the tumor [14][15][16][17]25 . Previous studies suggested that submucosal injection is superior than subserosal injection in intraoperative lymph node detection 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, there is still a global lack of high-level evidence-based medicine to determine whether ICG can help surgeons perform a safe and effective LN dissection. For this reason, the FUGES-012 study was conducted to assess the effectiveness of LN harvest and its safety during laparoscopic ICG-guided radical gastrectomy in patients with GC [52]. There were more retrieved LNs and lower LN noncompliance in the ICG group than in the non-ICG group, with a comparable recovery process.…”
Section: Application Of Indocyanine Green Fluorescence Imaging In Lg mentioning
confidence: 99%